Design considerations for pulsed-flow comprehensive two-dimensional GC: Dynamic flow model approach - PM Harvey; Robert Shellie; Paul Haddad (2010)
A dynamic flow model, which maps carrier gas pressures and carrier gas flow rates through the first dimension separation column, the modulator sample loop, and the second dimension separation column(s) in a pulsed-flow modulation comprehensive two-dimensional gas chromatography (PFM-GC×GC) system is described. The dynamic flow model assists design of a PFM-GC×GC modulator and leads to rapid determination of pneumatic conditions, timing parameters, and the dimensions of the separation columns and connecting tubing used to construct the PFM-GC×GC system. Three significant innovations are introduced in this manuscript, which were all uncovered by using the dynamic flow model. A symmetric flow path modulator improves baseline stability, appropriate selection of the flow restrictors in the first dimension column assembly provides a generally more stable and robust system, and these restrictors increase the modulation period flexibility of the PFM-GC×GC system. The flexibility of a PFM-GC×GC system resulting from these innovations is illustrated using the same modulation interface to analyze Special Antarctic Blend (SAB) diesel using 3 s and 9 s modulation periods.